A genome‐wide analysis suggests pleiotropic effects of Green Revolution genes on shade avoidance in wheat. (19th February 2022) - Colombo, Michel; Montazeaud, Germain; Viader, Véronique; Ecarnot, Martin; Prosperi, Jean‐Marie; David, Jacques; Fort, Florian; Violle, Cyrille; Fréville, Hélène
Abstract: A classic example of phenotypic plasticity in plants is the suit of phenotypic responses induced by a change in the ratio of red to far‐red light (R∶FR) as a result of shading, also known as the shade avoidance syndrome (SAS). While the adaptive consequences of this syndrome have been extensively discussed in natural ecosystems, how SAS varies within crop populations and how SAS evolved during crop domestication and breeding remain poorly known. In this study, we grew a panel of 180 durum wheat ( Triticum turgidum ssp. durum ) genotypes spanning diversity from wild, early domesticated, and elite genetic compartments under two light treatments: low R:FR light (shaded treatment) and high R:FR light (unshaded treatment). We first quantified the genetic variability of SAS, here measured as a change in plant height at the seedling stage. We then dissected the genetic basis of this variation through genome‐wide association mapping. Genotypes grown in shaded conditions were taller than those grown under unshaded conditions. Interaction between light quality and genotype did not affect plant height. We found six QTLs affecting plant height. Three significantly interacted with light quality among which the well‐known Rht1 gene introgressed in elite germplasm during the Green Revolution. Interestingly at three loci, short genotypes systematically expressed reduced SAS, suggesting a positive genetic correlation between plant height and plant height plasticity. Overall, our study sheds light on the evolutionary history of crops and illustrates the relevance of genetic approaches to tackle agricultural challenges.